THE WAYS OF MAKING METAFORA OF SYNTAX UNITS (ON THE EXAMPLE OF SHAVKAT RAHMON’S WORK) - Durdona, Yunusova Axtamovna (INTERNATIONAL CONFERENCES, 2022)
The article discusses the origin of metaphor in the communication system, its semantic nature, the phenomenon of metaphorization, metaphor and adjectivalization. Shavkat Rahmon’s poetry also analyzes the linguistic possibilities and syntactic-stylistic relations of metaphor formation.